Feminization of Agriculture: Reflections from the Female Participation in Training Programmes on Agriculture and Allied Activities - Manisha Bhatia and Jugraj Singh Marok (Journal of Krishi Vigyan, 2015)
Women are actively involved in agriculture and contribute significantly in agriculture and allied activities. Despite their active involvement in all aspects of agriculture like crop selection, land preparation, seed selection, cold storage handling, marketing and processing, their work is unorganized, unvalued and unrewarded. Active involvement of women in agriculture clearly indicates the feminization of agriculture referring to increasing presence or visibility in agriculture labour force, whether as agricultural worker, independent producers or unremunerated family workers. Is this trend of visibility of women in agriculture equally visible when it comes to capacity building of farmers? Is women participation in training programmes proportionate to their participation in agriculture and allied activities? The present paper was an attempt to find an answer to this by looking at the various vocational trainings conducted in the field of agriculture and allied activities from gender lens. The trainings conducted in the field of poultry, dairy, bee-keeping, mushroom cultivation and agricultural engineering during the last five years (2010-2014) in Krishi Vigyan Kendra, Shaheed Bhagat Singh Nagar were analyzed. The study indicated that although the participation of females in training programmes related to agriculture and allied activities has increased especially in dairy and mushroom cultivation but it was not in proportion and according to the rate of participation of females in agriculture or their representation in the population